Aspek-Aspek Mu’amalah Dalam Ekonomi Islam - Imam Sucipto (STAI Siliwangi Bandung, 2016)
The aspects of muamalah in Islamic economics broadly as follows: Assets, Properties, Functions of Money and 'Ukud (contract-contract), Buyu' (about sale and purchase), Ar-Rahn (about mortgages), Hiwalah (transfer of debt), Ash-Shulhu (peace business), Adh-Dhaman (guarantees, insurance), Syirkah (of the partnership), Wakalah (of representation), Wadi'ah (of care), 'Ariyah (on loan), Ghasab (seizure of the assets of others with no shah), Syuf'ah (right precedence in syirkah ground or equivalent), Mudharabah (syirkah capital and labor), Musaqat (syirkah in watering the garden), muzara'ah (agricultural cooperative), Kafalah (underwriting), Taflis (fall bankrupt), Al-Hajru (limitation act), Ji'alah (competition, granting fee), Qaradh (pejaman), Ba'I Murabahah, Ba'i Salam, Ba'I Istishna ', Ba'i muajjal and Ba'i Taqsith, Ba'i Sharf and foreign exchange transactions, 'Urbun (Retainer / DP), Ijarah (lease), Riba, the concept of money and monetary policy, Shukuk (bonds or bonds), Faraidh (legacy), Luqthah (items scattered), Waqf, Grant, Washiat, Iqrar (confession), Qismul fa'i wal Ghanimah (division fa'i and ghanimah), Qism ash-Shadaqat (on the division of zakat), Ibrak (debt relief), Muqasah (Discount).